Mantle Flow and Dynamics Beneath Central‐East China: New Insights From P‐Wave Anisotropic Tomography. Issue 5 (25th May 2021) - Jiang, Guoming; Zhang, Guibin; Zhao, Dapeng; Lü, Qingtian; Shi, Danian; Li, Hongyi; Li, Xinfu
Abstract: Massive lithospheric thinning occurred in eastern China and large‐scale magmatism in South China occurred in the Mesozoic. Some geodynamic models have been proposed to explain their mechanisms, but are not consistent with each other. We apply anisotropic tomography to 32, 728 P ‐wave travel time data of 479 teleseismic events recorded at 225 stations to study the 3‐D anisotropic Vp structure of the upper mantle beneath central‐east China. P ‐wave radial anisotropy is investigated for the first time in the study region. Our results show that an obvious low‐velocity zone exists in the asthenosphere under the eastern part of our study region, which represents upwelling thermal flow from the Cathaysia block to the North China block (NCB) according to the results of azimuthal and radial anisotropies. A distinct high‐velocity zone with weak radial anisotropy exists under the middle Yangtze block, which is explained as the stable cratonic root. Two other weak high‐velocity zones appear near or within the mantle transition zone under the middle‐lower Yangtze River and the eastern NCB, which might be detached lithosphere or the stagnant Pacific slab. Combining with previous geological and geochemical results, we consider that both the NCB and the South China block have undergone a common geodynamic process in the Mesozoic due to their similar age trending of igneous rocks, which could be explained by a flat‐slab subduction model and a ridge subduction model. These two models are associated with the paleo‐Pacific plate subduction that might have played a key role in the evolution of eastern China. Key Points: Anisotropic tomography is applied to study the 3D anisotropic velocity structure under central‐east China Mantle flow with low P ‐wave velocity upwells and moves from the Cathaysia block to the North China block The paleo‐Pacific plate subduction might have prompted the thermal material migration